1994
DOI: 10.2527/1994.7271754x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bulky diets based on wheat bran or oat hulls on reproductive performance of sows during their first two parities1

Abstract: The aim of the present study was to determine the effect of different degrees of bulkiness in the gestation diet on reproductive performance of sows during their first two parities. The density of the diets was modified by incorporating a high proportion of fibrous ingredients (wheat bran and corn cobs in Diet 2 and oat hulls and oats in Diet 3). A diet without fibrous ingredients was used as a control (corn and soybean meal in Diet 1). Although all the gestation diets were formulated to provide the same daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 14 publications
9
42
2
Order By: Relevance
“…Differences in backfat thickness at weaning did not influence the subsequent weaning-to-oestrus interval. The lack of effect of dietary fibre on the weaning-to-oestrus interval is consistent with the previous results reported in literature (Matte et al, 1994;Farmer et al, 1996;Vestergaard and Danielsen, 1998;Holt et al, 2006). Some differences were found between trials or replicates in backfat thickness without any clear pattern to explain theses effects.…”
Section: --supporting
confidence: 92%
See 2 more Smart Citations
“…Differences in backfat thickness at weaning did not influence the subsequent weaning-to-oestrus interval. The lack of effect of dietary fibre on the weaning-to-oestrus interval is consistent with the previous results reported in literature (Matte et al, 1994;Farmer et al, 1996;Vestergaard and Danielsen, 1998;Holt et al, 2006). Some differences were found between trials or replicates in backfat thickness without any clear pattern to explain theses effects.…”
Section: --supporting
confidence: 92%
“…However, Matte et al (1994) found that during their second parity, sows fed a gestation diet based on wheat bran and maize cobs gave birth to heavier piglets than sows fed diets based on maize and soya-bean meal, or on oat hulls and oats. These piglets were also heavier at weaning.…”
Section: --mentioning
confidence: 96%
See 1 more Smart Citation
“…Some literature had observed that NSP-rich diets reduce physical activity of growing-finishing pigs (Schrama et al, 1996(Schrama et al, & 1998 and sows (Brouns & Edwards, 1994;Matte et al, 1994). Additionally, Brooks and Murray (unpublished data) observed significant differences in the behavior of pigs fed fermented and non-fermented diets.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has reported a 20% increase in the growth rate of piglets when gestating sows were fed a fiber diet compared with sows fed a control diet but this effect was observed during the second cycle of lactation and not the first (Matte et al, 1994). Therefore, additional research directed at feeding KF diets to gestating sows could entail an evaluation of the effects of KF on sows for more than one reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%